PENERAPAN ICE BREAKER GAME UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Sirait, Syahriani; anim; elfira rahmadani; ely Syafitri (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2023)
This research aims to determine the increase in student learning motivation after implementing the ice breaker game in learning. The research method used is mixed. The research respondents were fifth grade students at SDN 010246 Banjar. Data was collected using the questionnaire method. The research results show that the application of the ice breaker game can increase student learning motivation in the sufficient category, meaning that there is a positive contribution from the ice breaker game to student learning motivation. This research can be developed in other mathematics learning